ANALISIS KESEHATAN BANK PERKREDITAN RAKYAT STUDI KASUS PADA PERUSAHAAN DAERAH BPR BKK KECAMATAN SEDAN KABUPATEN REMBANG DARI TAHUN 2000 SAMPAI DENGAN 2005 - Mokhamat Ansori (STIE Pelita Nusantara Semarang, 2006)
By mean of this study, the writer would like to investigate the level of financial health of a Bank Prekreditan Rakyat in Rembang where the writer used to be a staff in the Bank mentioned. The Financial Health Report is an important mean in obtaining the information related to the achievements of the bank in a certain period. The information would be beneficial for the parties as the owner and the customers. Further decisions taking, will also based on this financial helathreport.With the reason of the increased competition among banks and other financial organizations, the PD. BPR BKK Sedan should improve its market by mean of directed and offensive services improvements. The analysis will be incredibly needed before the bank release a credit to customers. The financial health condition of PD. BPR BKK Sedan, might be seen from four aspects of ratio;Return on Assets (ROA), Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), and the Non Performing Loan (NPL). For the writer's objectives, the writer would like to analyze those four aspects of ratio from the year of 2000 to 2005.